The prognostic and pathophysiologic role of pro- and antiinflammatory cytokines in severe malaria. - Day, N; Hien, T; Schollaardt, T; Loc, P; Chuong, L; Chau, T; Mai, N; Phu, N; Sinh, D; White, N; Ho, M (1999)
Pro- and antiinflammatory cytokines were measured on admission in 287 consecutive Vietnamese adults with severe falciparum malaria. Plasma interleukin (IL)-6, IL-10, and tumor necrosis factor (TNF)-alpha concentrations and the IL-6: IL-10 ratio were significantly higher in patients who died than in survivors (P<.001). On multivariate analysis, hyperparasitemia, jaundice, and shock were all associated independently with raised IL-6, IL-10, and interferon-gamma, and acute renal failure specifically with raised TNF-alpha levels. Cerebral malaria patients, particularly those without other vital organ dysfunction, had significantly lower levels of these cytokines (P=.006), reflecting a more localized pathology. Serial IL-6 and IL-10 measurements made on 43 patients who died and matched survivors indicated a relative deficiency in IL-10 production as death approached. Elevated plasma cytokines in severe malaria are associated with systemic pathologic abnormalities, not cerebral involvement. Both the overall magnitude of the cytokine responses and the eventual imbalance between the pro- and antiinflammatory responses are important determinants of mortality.